ISSUES OF IMPROVING DEBT BURDEN IN LENDING TO INDIVIDUALS - Yakshimuratova Khasiyat Khudaybergenovna (Scholars Digest Publishing, 2025)
This article analyzes the formation of the debt burden in the system of lending to individuals, methods of its assessment and areas for improvement. Today, as the population's need for credit resources increases, there is an increasing need to develop a lending policy taking into account their financial stability and solvency. During the study, the criteria for measuring the debt burden, international experience, debt burden indicators introduced in the banking system of Uzbekistan and their effectiveness were considered. In particular, the debt burden restrictions established by the Central Bank and their impact on the financial behavior of the population were studied. In addition, proposals were developed on alternative methods of assessing credit risks in conditions of low income formalization, the introduction of a credit rating system, increasing financial literacy and making credit terms transparent.
Keywords: Lending to individuals, debt burden, credit burden, credit risks, credit solvency, interest rate, financial literacy, bank loans, microloans, consumer loans.